Intraductal magnetic resonance imaging of cholangiocarcinoma - a practical possibility - Syms, Richard R. A.; Wadsworth, Christopher A.; Kardoulaki, Evdokia; Titapun, Attapol; Boonphongsathien, Wuttisak; Sa-Ngiamwibool, Prakasit; Zhang, Shuo; Taylor-Robinson, Simon D.; Chamadol, Nittaya; Loilome, Watcharin (Frontiers in Oncology, 2024)
Intraductal T2 mapping based on a catheter receiver is proposed as a method of visualizing the extent of intraductal and periductal cholangiocarcinoma (CCA). Compared to external receivers, internal receivers provide locally enhanced signal-to-noise ratios by virtue of their lower field-of-view for body noise, allowing smaller voxels and higher resolution. However, inherent radial sensitivity variation and segmentation for patient safety both distort image brightness. We discuss simulated T2 weighted images and T2 maps, and in vitro images obtained using a thin film catheter receiver of a freshly resected liver specimen containing a polypoid intraductal tumour from a patient with CCA. T2 mapping provides a simple method of compensating non-uniform signal reception patterns of catheter receivers, allowing the visualization of tumour extent without contrast enhancement and potentially quantitative tissue characterization. Potential advantages and disadvantages of in vivo intraductal imaging are considered.